Experimental and numerical research on the nonlinear creep response of polymeric composites under humid environments. (1st November 2020) - Sun, Tongsheng; Yu, Cungui; Yang, Wenchao; Zhong, Jianlin; Xu, Qiang
Abstract: The aim of this work is to study the nonlinear creep response of polymeric composites under humid environments. A three-dimensional orthotropic nonlinear creep constitutive model that considers the moisture effect is derived by introducing the moisture shift factor into Schapery's nonlinear equation. Hygrothermal-mechanical coupling moisture absorption tests, as well as static mechanical property tests and short-term tensile creep-recovery tests with different moisture contents were performed to obtain the hygroscopic parameters and the moisture and stress dependent nonlinear creep parameters. A fully coupled numerical prediction model was developed in Abaqus with a user-defined material subroutine (UMAT) and user-defined field variable subroutine (USDFLD) to simulate the coupled diffusion-nonlinear creep behaviour. Good agreement was observed between the numerical and experimental results.